GALICS: Capturing the panchromaticity of galaxies - Devriendt, J (2002)
This contribution describes results obtained with the GALICS model (for Galaxies In Cosmological Simulations), which is a hybrid model for hierarchical galaxy formation studies, combining the outputs of large cosmological N-body simulations with simple, semi-analytic recipes to describe the fate of the baryons within dark matter halos. Designed to predict the overall statistical properties of galaxies, with special emphasis on the panchromatic spectral energy distribution emitted by galaxies in the UV/optical and IR/submm wavelength ranges, such an approach can be used to predict the galaxy luminosity function evolution from the ultraviolet to far infrared, along with individual galaxies star formation histories.